(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article analyzes modern methods of using digital technologies in student education and their impact on the educational process. The research examines the influence of digital tools on teaching methodology, their effect on students’ learning levels, and their role in the pedagogical process. The article reviews the effectiveness of multimedia technologies, interactive programs, electronic educational resources, and modern teaching platforms. Research results indicate that proper application of digital technologies plays a crucial role in improving students’ knowledge quality, enhancing motivation, and developing independent learning skills. The article is intended for pedagogical scholars, teachers, and educational technology specialists.